Evaluation of the biofunctionality of the addition of silver on anodized surface of AISI 316L steel (Research, Society and Development, 2022)
AISI 316L austenitic stainless steel is a material already widely used in medicine, mainly in public health systems due to its high availability and low cost. This study aims to improve the biocompatibility properties of this material. AISI 316L samples were anodized with 10M NaOH electrolyte, current density of 0.6 mA.cm-2 for 5 and 10 minutes. The sample anodized for 5 minutes had silver added to the surface. Anodized surfaces were analyzed by scanning electron microscopy (FESEM/EDS), atomic force microscopy (AFM), contact angle. The biofunctionality assays encompassed the formation of hydroxyapatite, cytotoxicity and bactericidal and antifungal action. The results showed a nanorough anodized layer with hydrophilicity and satisfactory biofunctionality for use as a biomaterial. However, the samples with silver did not show a satisfactory result of bactericidal action. The most satisfactory performance achieved in the characterizations was presented by the sample anodized for five minutes in relation to the roughness property, showing good results for the formation of hydroxyapatite. In this way, this layer obtained shows itself as a promising alternative for future applications in biomedical areas when compared to the original AISI 316L steel currently used for these functionalities.